Relationship Between Employee Wages, Number of Employee Referrals, and Employee Turnover Intention - Brown, Robert (2018)
Employee turnover is a significant contributor to the overall loss of hundreds of billions of dollars in profitability for many business organizations in the United States and abroad combined. Grounded in Maslow's theory of human motivation, the purpose of this correlational study was to examine the relationship between employee wages, number of employee referrals, and employee turnover intentions. The population was composed of employees working in the Southeastern region of the United States. A convenience sample of 92 participants answered questions regarding their wages, number of employee referrals, and completed the Turnover Intention Scale. Results of the multiple regression analysis indicated the model as a whole was able to significantly predict turnover intentions, F(2, 89) = 5.462, p = .006, R2 = .109. Within the final model, employee wages was a statistically significant predictor (t=-2.769, p=.007) and the number of employee referrals was not a statistically significant predictor (t=-1.712, p=.090). The knowledge gained from the findings in this study could have implications for social change among employees and consumers in society. Satisfied employees in low turnover work environments can provide the foundation for a more enjoyable customer experience. Both non-profit and for-profit organizations can implement business practices that will reduce turnover and increase job satisfaction among employees